2020
DOI: 10.1038/s41467-020-16930-1
|View full text |Cite
|
Sign up to set email alerts
|

Setting benchmarks for modelling gas–surface interactions using coherent control of rotational orientation states

Abstract: The coherent evolution of a molecular quantum state during a molecule-surface collision is a detailed descriptor of the interaction potential which was so far inaccessible to measurements. Here we use a magnetically controlled molecular beam technique to study the collision of rotationally oriented ground state hydrogen molecules with a lithium fluoride surface. The coherent control nature of the technique allows us to measure the changes in the complex amplitudes of the rotational projection quantum states, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 67 publications
0
50
1
Order By: Relevance
“…A first measurement of a scattering matrix was demonstrated recently for hydrogen molecules scattering from an LiF surface. 189 The results of this study demonstrated that this simple salt surface acts as both a rotational orientation polarizer and a rotational orientation analyser for hydrogen molecules, and the extracted scattering matrix elements provide what is arguably the most sensitive experimental bench mark for further development of theoretical molecule-surface interaction potentials.…”
Section: Applying Helium Scattering Instruments For Molecularsurface Scattering and Other Atom-surface Scattering Experimentsmentioning
confidence: 82%
“…A first measurement of a scattering matrix was demonstrated recently for hydrogen molecules scattering from an LiF surface. 189 The results of this study demonstrated that this simple salt surface acts as both a rotational orientation polarizer and a rotational orientation analyser for hydrogen molecules, and the extracted scattering matrix elements provide what is arguably the most sensitive experimental bench mark for further development of theoretical molecule-surface interaction potentials.…”
Section: Applying Helium Scattering Instruments For Molecularsurface Scattering and Other Atom-surface Scattering Experimentsmentioning
confidence: 82%
“…However, in our experimental setup we cannot select the initial state of the molecular orientation as has been done in other molecular beam studies, where it was shown that the alignment of an incident diatomic molecule strongly influences the angular distribution of the scattered molecules, the energy loss during the collision and the trapping probability. 8,[28][29][30][31] In summary, the sampled surface corrugation, which plays a crucial role in RID, is affected by both the azimuthal and molecular orientations. Our measurements can address the former, however, our experimental setup does not allow us to address the latter.…”
Section: Resultsmentioning
confidence: 99%
“…This should be possible as in the case of the experiments, the only unknown in eqn (1) and ( 2 can provide enough information to allow the scattering matrix to be extracted from the data, similarly to what has been achieved with 1d data measured for diffractive scattering. 20 Applying new machine learning algorithms, for example Gaussian Process models, 22 could potentially reduce the number of B 1 and B 2 values that would be required to obtain an empirical scattering matrix in this way. The scattering matrices that we extract not only provide a new and stringent benchmark which will help guide the development of accurate theoretical models of gas-surface collisions, but also provide m J state to m J state scattering probabilities, which in turn can be used to determine to what extent collisions of H 2 with the surface rotationally polarise the scattered molecular beam.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments are capable of extracting the scattering matrix from the data, a unique observable which describes the changes in the quantum wavefunctions that occur during scattering. 20 In contrast, when measuring under more general scattering conditions, including specular scattering, the full width of the velocity distribution of the beam particles contributes to the signal. In this case we need to find conditions where the velocity dependence of the magnetic moment is not important up to first order and the averaging over the beam particles results in a finite signal, i.e., the spin echo phenomena.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation